Potret Kuota Perempuan di Parlemen - Ratnawati, - (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
In response to the slow progress in improving women role in politics, an affirmative action has been adopted in Indonesia. A scheme, which popularly known as "quota 30% for women in parliament," has been well-advocated, despite it retains controversy. This article makes a brief look at the respond of political parties to that scheme and identifes the challenge lays ahead.